Introducing the business model canvas: A practical tool for young entrepreneurs at SMA Al Azhar 19 Ciracas - Supriyadi Thalib; Harimurti Wulandjani; Erwin Permana; Irma Sari Permata; Chaerani Nisa; Irdan Hadikusuma; Winda Nurul Pebriyani (Journal of Community Service and Empowerment)
This community development program aimed to equip Gen Z students at SMA Al Azhar 19 Ciracas with essential entrepreneurial competencies, focusing on the application of the Business Model Canvas (BMC) as a fundamental tool for business planning and development. To achieve these objectives, the program employed a blended approach that combined theoretical instruction with practical, interactive activities. The initiative commenced with a preliminary assessment to evaluate the students' baseline understanding, followed by dynamic lectures, workshops, and the incorporation of interactive games to ensure high levels of engagement and active participation. The program enabled students to apply the BMC framework to their own business ideas, supported by continuous feedback from mentors, fostering iterative learning and improvement. Results demonstrated significant enhancements in the students’ understanding and ability to develop and communicate their business concepts effectively. Furthermore, the program’s findings have practical applications, as the students are now better prepared to utilize the BMC in real-world scenarios, driving innovation and entrepreneurship within their communities. In conclusion, this initiative not only improved entrepreneurial education by nurturing creativity, critical thinking, and problem-solving skills but also contributed to the students’ readiness for future business endeavors, ultimately supporting their roles as innovative contributors to their local economy.